1972
DOI: 10.1128/jvi.10.2.171-178.1972
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Ribonucleic Acid and Deoxyribonucleic Acid Viruses to Different Species of Interferon in Cell Cultures

Abstract: Although two deoxyribonucleic acid (DNA) viruses, pseudorabies (PsRV) and vaccinia, are as susceptible as a ribonucleic acid (RNA) virus, vesicular stomatitis (VSV), to interferon when tested in chicken or mouse cells, they are refractory to inhibition in interferon-treated primary rabbit kidney cells and in a continuous line (RK-13) of rabbit kidney cells. Superinfection with VSV of RK-13 cells first infected with PsRV completely blocks the replication of PsRV with no effect on VSV yield. When the same experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…A plaque-p d e d preparation of VSV (Indiana serotype) was maintained for determination of antiviral state and IFN titration. Antiviral state was measured by infecting control and IFN-treated cells with VSV at an input multiplicity of infection (moi) of ten plaque-forming units (pfu) per cell; virus yield (pfdml) was quantitated by plaque assay in L-929 cells according to methods we have previously described (Youngner et al, 1972). Results are reported as mean (?…”
Section: L-tmentioning
confidence: 99%
“…A plaque-p d e d preparation of VSV (Indiana serotype) was maintained for determination of antiviral state and IFN titration. Antiviral state was measured by infecting control and IFN-treated cells with VSV at an input multiplicity of infection (moi) of ten plaque-forming units (pfu) per cell; virus yield (pfdml) was quantitated by plaque assay in L-929 cells according to methods we have previously described (Youngner et al, 1972). Results are reported as mean (?…”
Section: L-tmentioning
confidence: 99%
“…A product of 2',5'-oligoisoadenylate synthetase activates an endoribonuclease, thereby leading to the increased degradation of viral mRNAs (27,71,256,395); this process may be inhibited by virusinduced ATPase and phosphatase or inhibition of the endoribonuclease (147,353,398). Additional support for the existence of virus genes which modify the antiviral effects of interferon came from the studies of Youngner et al (519), who showed that prior infection of RK-13 cells with vaccinia virus was able to partially reverse the interferon-mediated inhibition of vesicular stomatitis virus replication. The biological significance of these observations to a natural poxvirus infection is self-evident (see the subsection on interferons in Nonspecific Host Responses to Infection, below).…”
Section: Inhibition Of Host Defense Mechanismsmentioning
confidence: 99%
“…These involvements could also explain the findings that in vitro sensitivities of a virus to interferon (antiviral) actions does not necessarily correlate with the in vivo sensitivities of the virus to interferon actions. Vaccinia virus, which is quite resistant to interferon action in rabbit cell cultures Youngner et al, 1972), was found to be affected by rabbit interferon in rabbit skin (Isaacs and Westwood, 1959b) and rabbit eyes (Cantell and Tommfla, 1960;Oh and Yoneda, 1969). Herpesvirus is quite insensitive to interferon in many in vitro systems, but appears to be very sensitive in the eye.…”
Section: Interferon Mechanisms and Pathogenesismentioning
confidence: 99%